INFLUENCE OF POLYPHARMACY ON THE FUNCTIONAL ABILITY OF PATIENTS WITH RHEUMATOID ARTHRITIS - Krstić, Nikola; Stefanović, Nikola; Gocić, Valentina; Ilić, Katarina; Damnjanović, Ivana (Acta medicae Medianae, 2023)
Clinical guidelines for the treatment of rheumatoid arthritis (RA) are based on the use of: nonsteroidal anti-inflammatory drugs (NSAIDs), conventional disease-modifying drugs (csDMARDs), immunosuppressants and biological therapies. Unfortunately, a large number of patients have other chronic diseases in addition to RA, which requires additional multiple use of drugs and often leads to polypharmacy. According to the definition of the World Health Organization (WHO), polypharmacy is defined as the routine use of 5 or more drugs, including prescription of over-the-counter drugs, dietary supplements, and traditional medicines. The aim of the study was to examine the impact of polypharmacy on the functional ability of patients with RA estimated based on the HAQ-DI index.A retrospective study included 131 patients diagnosed with RA. Within the clinical characteristics, attention was focused on the present comorbidities, therapy and the total number of drugs used. The HAQ questionnaire was used to assess health status and functional ability. The obtained data were analyzed and statistically processed using appropriate software and statistical methods.The study involved 29 males and 102 females mean age 60.25 ± 11.21 years. The analysis of the collected clinical data showed the presence of comorbidities in 80.15% of patients. Synthetic disease-modifying drugs were used 88.55%, while 13.74% of patients were on biological therapy. HAQ-DI values < 1.5 were present in 83.21%, while HAQ-DI ≥ 1.5 values were recorded in 16.79% of respondents. Polypharmacy was present in 75.57% of respondents. Potential interactions were more frequent in the group of respondents who can perform normal physical activities without or with mild restrictions (HAQ-DI < 1.5), while the presence of one serious potential interaction was more pronounced in the group of respondents with reduced functional ability (HAQ-DI ≥ 1.5).The results of this study show a high frequency of polypharmacy and consequent potential drug interactions in patients with RA. Accordingly, monitoring of polypharmacy in patients with RA is necessary in order to achieve optimal functional status, disease control, minimize drug interactions and side effects.
Keywords: Polypharmacy; Rheumatoid arthritis; HAQ-DI